Motivasi dan Keterlibatan Audiens dalam Live streaming YouTube Windah Basudara - Sulistyo, Bagus Aditya; Mardiana, Lisa (Jurnal Audiens, 2026)
This study was conducted to describe audience engagement in the YouTube live streaming of Windah Basudara. The development of the YouTube platform enables direct engagement between creators and audiences through live chat and comment features. This research employed a qualitative approach using the transcendental phenomenology method. Data were collected through observations of audience activities during live streaming sessions from 2025 and in-depth interviews with 12 informants who were viewers of the channel. Data analysis was conducted using the phenomenological stages proposed by Moustakas. This study applied Audience Engagement Theory and Uses and Gratifications Theory to understand the levels of engagement and audience motivations. The findings indicate that audience engagement is divided into three levels: primary, secondary, and tertiary engagement. The results also show that live streaming functions not only as a medium of entertainment but also as a space for digital social interaction that strengthens emotional engagement and collective audience participation. This study enriches the discourse on audience engagement in the context of YouTube live streaming through a phenomenological approach.